Mast Cell Counts and Microvessel Density Expressions in Hodgkin's Lymphoma and Reactive Lymphadenopathy in Children - Derya Özyörük; Esra Karakuş; Suna Emir; Arzu Yazal Erdem; Melek Işık (Galenos Publishing House, 2022)
Objective: Mast cells (MCs) have been shown to make a significant contribution to both normal and tumorassociated neo-angiogenesis. The aim of this study is to analyse the relationship between microvessel density (MVD) and MCs in tissues of children with Hodgkin's lymphoma (HL) and reactive lymphadenopathy (RL). Method: This retrospective study was conducted with 29 newly diagnosed HL patients and 30 patients with RL. MCs and microvascular density expressions were studied immunohistochemically in the tissues obtained from formalin-fixed and paraffin embedded blocks of archival specimens in our clinic. Results: The mean MC count in HL was higher compared to the RL group (p<0.001). MVD expression in HL was lower than RL (p<0.001). In RL group, MC counts were correlated with MVD expression (r=-0.055, p>0.05). MC counts in nodular sclerosis subgroup were higher compared to mixed cellularity subgroup (p<0.05). In HL group, MC counts were positively correlated with age and nodular sclerosis histology, and negatively correlated with serum lactate dehydrogenase enzyme levels. Microvascular density expressions were positively correlated with advanced stages. Conclusion: Our data suggest that MCs may have limited contribution to angiogenesis in childhood HL rather than RL group.